2020
DOI: 10.21203/rs.2.18340/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

miR-373-3p inhibits EMT via regulation of TGFβR2 in choriocarcinoma

Abstract: Background: Previous studies have indicated that early metastasis is a major cause of mortality in patients with choriocarcinoma. However, what determines whether early metastasis of choriocarcinoma has occurred is unknown. The emerging role of miRNA in regulating cancer development and progression has been recognized. MiR-373 has been shown to play pivotal roles in tumorigenesis and metastasis. However, whether miR-373 functions to promote choriocarcinoma metastasis is not clear. The purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…e findings showed that ASP dose-dependently boosted the miR-373-3p level in glioma cells. MiR-373-3p is a specific miRNA that plays a dual role in different types of cancers [15][16][17][18][19][20][21][22]. miR-373 expression has been shown to be reduced in glioma tissues, which is associated with WHO grade, KPS score, poor overall survival, and progression-free survival [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…e findings showed that ASP dose-dependently boosted the miR-373-3p level in glioma cells. MiR-373-3p is a specific miRNA that plays a dual role in different types of cancers [15][16][17][18][19][20][21][22]. miR-373 expression has been shown to be reduced in glioma tissues, which is associated with WHO grade, KPS score, poor overall survival, and progression-free survival [23].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-373-3p is an oncomiRNA that is upregulated in diverse cancers, for instance, lung adenocarcinoma [15], tongue squamous cell carcinoma [16], testicular germ cell tumor [17], and esophageal squamous cell carcinoma [18]. On the contrary, miR-373-3p can also act as an antioncomiRNA in pancreatic carcinoma [19], choriocarcinoma [20], hepatocellular carcinoma [21], cervical carcinoma [22], and glioma [23][24][25]. Jing et al proved that the miR-373 level is reduced in glioma tissues [23].…”
Section: Introductionmentioning
confidence: 99%